Depression or Anxiety by Region, Small-Area Deprivation, and Health Care Level in Sweden - Emily White Johansson; Ahmed Nabil Shaaban; Anna Ohlis; Mathias Mattsson; Lode van der Velde; Susanne Wicks; Christina Dalman; Emilie E. Agardh (JAMA Network Open, 2026)
Importance There is a lack of comprehensive evidence on the burden and management of depression or anxiety in health care systems that leverage multiple health care and prescription registers, including primary care datasets in which these conditions typically first present. Objective To examine the distribution of depression or anxiety among people 10 years or older in Sweden by region, small-area deprivation, and health care level of first diagnosis. Design, Setting, and Participants This nationwide, register-based, cross-sectional study included people aged 10 years or older who were living in Sweden from January 1, 2015, to December 31, 2023. Data were analyzed from January to June 2026. Exposure Small-area deprivation was defined for 5984 small geographic areas in 2015 using a published Index for Multiple Deprivation in Sweden categorized into quartiles. Main outcomes and measures Depression or anxiety was defined as the first diagnosis, or first prescription date if no diagnosis was recorded in the study period. Crude and age-standardized rates of depression or anxiety per 1000 persons were tabulated at national and subnational levels. Multilevel logistic regression quantified associations between small-area deprivation and the outcome adjusted for confounders. Health care level for the first diagnosis was compared by region, small-area deprivation, and patient characteristics. Results Among 8 528 198 individuals aged 10 years or older (50.2% female), 2 087 413 had recorded depression or anxiety between 2015 and 2023, corresponding to a rate of 244.8 (95% CI, 244.4-245.1) cases per 1000 persons. Higher odds of depression or anxiety were found in the most vs least deprived areas (OR, 1.18; 95% CI, 1.16-1.20). Among 1 359 196 patients with depression and anxiety between 2015 and 2017, 56.2% (95% CI, 56.1%-56.3%), 18.1% (95% CI, 18.0%-18.1%), and 3.2% (95% CI, 3.2%-3.2%) were first diagnosed in primary, outpatient, and inpatient care, respectively. Conclusions and Relevance This cross-sectional study using administrative registers found lower rates of depression or anxiety among residents of Sweden than reported in population surveys, likely due to underestimating individuals not seeking health care. Higher odds of depression or anxiety in most vs least deprived areas could underscore the association of these conditions with socioeconomically disadvantaged contexts. Variation by region and patient characteristics in the health care level for first diagnosis merits further investigation.